Teknik Distraksi Audio Visual Menurunkan Tingkat Kecemasan Anak Usia Sekolah yang Menjalani Sirkumsisi - Farida Juanita (Universitas Airlangga, 2007)
Introduction: Circumcision is one of minor surgery that usually done for school age children. Most of the children appear to be anxious enough. Audio-visual distraction is one of the methods that researcher want to applied to decrease children’s anxiety level during circumcision. The objective of this study was to identify the effect of audio-visual distraction to decrease children’s anxiety level during circumcision. Method: Non randomized pretest-posttest control group design was used in this study. There were 21 children divided into two groups, control group (n=13) receive intervention as usual, otherwise the intervention group (n=8) receive audio-visual distraction during circumcision. By using self report (scale of anxiety) and physiological measures of anxiety (pulse rate per minute), children are evaluated before and after the intervention. Result: The result showed that audio-visual distraction is efective to decrease the anxiety level of school age children during cicumcision with significance difference on the decrease of anxiety level between control and intervention group (p=0.000) and significance difference on the pulse rate per minute between control and intervention group (p=0.006). Discussion: It can be concluded that by applying the audio-visual distraction during circumcision could be minimized the children’s anxiety. The audio visual is needed for children to manage and reduce anxiety during invasive therapy through mecanism of distraction.